The art of assembly language programming using PIC technology : core fundamentals - Schousek, Theresa (Newnes, an imprint of Elsevier, 2018)
The Art of Assembly Language Programming using PICª Technology thoroughly covers assembly language as used in programming the PICª Microcontroller (MCU). Using the minimal instruction set, characteristic of most PICª products, the author elaborates on the nuances of how to execute loops. Fundamental design practices are presented based on Orr's Structured Systems Development using four logical control structures. These control structures are presented in Flowcharting, Warnier-Orrª diagrams, State Diagrams, Pseudocode, and an extended example using SysMLª. Basic math instructions of Add and Subtract are presented, along with a cursory presentation of advanced math routines provided as proven Microchipª utility Application Notes. Appendices are provided for completeness, especially for the advanced reader, including several Instruction Sets, ASCII character sets, Decimal-Binary-Hexadecimal conversion tables, and elaboration of ten 'Best Practices.' Two datasheets (one complete datasheet on the 10F20x series and one partial datasheet on the 16F88x series) are also provided in the Appendices to serve as an important reference, enabling the new embedded programmer to develop familiarity with the format of datasheets and the skills needed to assess the product datasheet for proper selection of a microcontroller family for any specific project. The Art of Assembly Language Programming Using PICª Technology is written for an audience with a broad variety of skill levels, ranging from the absolute beginner completely new to embedded control to the embedded C programmer new to assembly language. With this book, you will be guided through the following areas: Symbols and terminology used by programmers and engineers in microcontroller applications Programming using assembly language through examples Familiarity with design and development practices Basics of mathematical knowledge in hexadecimal Resources for advanced mathematical functions Approaches to locate resources.